MULTIPLE RETINAL PIGMENT EPITHELIUM APERTURES ASSOCIATED WITH PSEUDO-VITELLIFORM LYMPHOMATOUS MACULOPATHY. Issue Volume 16:Issues 1(2022) (28th November 2019) - Cicinelli, Maria Vittoria; Marchese, Alessandro; Miserocchi, Elisabetta; Querques, Giuseppe; Bandello, Francesco; Modorati, Giulio M.
Abstract : The authors report a pseudo-vitelliform subretinal lesion associated with multiple retinal pigment epithelium apertures in vitreoretinal lymphoma; the case might represent a sign of macular infiltration, a paraneoplastic maculopathy, or coexistence of both. Retinal pigment epithelium apertures are a novel finding in vitreoretinal lymphoma. Abstract : Purpose: To describe the case of a 66-year-old man with bilateral cytologically proven vitreoretinal lymphoma who presented with a pseudo-vitelliform macular lesion and multiple retinal pigment epithelium apertures. Methods: The patient underwent comprehensive ophthalmologic evaluation, including best-corrected visual acuity, intraocular pressure, anterior segment and fundus examination, and optical coherence tomography, at baseline and during follow-up. Results: A new-onset foveal yellow, ill-defined lesion was noticed in the right eye during the follow-up; best-corrected visual acuity was 20/20, and the patient was asymptomatic. The lesion was isoautofluorescent with the surrounding retina. The optical coherence tomography revealed hyperreflective subretinal material, an irregularly thickened retinal pigment epithelium, and a shallow, hyperreflective retinal pigment epithelium detachment with multiple retinal pigment epithelium apertures. After 15 days, the lesion was completely reabsorbed and replaced by outer retinal atrophy and cystoid macular edema; best-corrected visual acuity dropped to 20/100. Conclusion: The macular lesion may be a sign of macular infiltration, a case of paraneoplastic cloudy vitelliform submaculopathy, or coexistence of both. Retinal pigment epithelium apertures are not disease-specific and are described in vitreoretinal lymphoma for the first time.